(1270) A geometrical proof for the duality theorem in linear programming برهان هندسي لنظرية الازدواجية في البرمجة الخطية - El-Kafrawy, M. (The Institute Of National Planning., 2018)
In surveying the literature which has been written since 1945, the year when Herbert A. Simon's Administrative Behavior was first edited, it becomes apparent that there is a linkup between Simon's theory and empirical research. This relationship between theory and research seems to be of two types.